Healthy Latrines Prevent Diarrhea as an Effort to Reduce STOP Defecation in Kutalimbaru Village, Deli Serdang Regency - M. Aslam Al Qadri Barito; Sri malem Indirawati; Mykel Johannes Situmeang; Fathiyah Aqila Hasibuan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The case of diarrhea reached 18.39% in the village of Kutalimbaru where the people are still having open defecation in the river. Open defecation causes clean water resources contaminated by e’coli bacteria since people in Kutalimbaru still use rivers as a source of clean water. 17,1% of the head of the family have not yet had a latrine while the public latrine facility in this village is no longer functioning. The methods used to solve the problems were community approach, diagnosis of action, socialization, education and action to build a healthy latrine in Dusun III Kutalimbaru. The built latrine was a model latrine. The latrine meets 10 indicators of a healthy latrine and is equipped with environmentally friendly innovations, has a fiber roof and has a vertical garden using used bottles. Evaluation is still ongoing to improve and maintain the sustainability program.